Evaluación de la actividad antibacteriana y antimicótica de tres extractos de la flor de hipobroma longiflora (L.) G. (Cholo valiente), por el método de difusión de agar - Rey Curay, Diego Michael (2013)
This research was conducted at the Chemical Analysis Laboratory of the National University of Loja, in the Laboratory of Microbiology and Phytochemistry Unit, in order to evaluate the antibacterial and antifungal activity of three extracts Hippobroma Flower longiflora (L.) G. Don (Cholo brave) by the agar diffusion method. In the province of Zamora Chinchipe plant was collected in study Hippobroma longiflora these are used by healers Shuar communities so the leaves are used to clean wounds and flowers are considered antipyretic and decongestant. Also one of the properties of this plant is considered as anti-inflammatory or analgesic, for some of the communities that also know how to use in some drinks because they have especially hallucinogens shamans. For this reason was routed to conduct this research in order to promote the ancestral knowledge of the Shuar communities in the Southern Region of Ecuador relying on clinical and safety enhancing technology of plants in different ethnic groups and have the tools to implement development strategies as these are not recognized scientifically. For this study three dilutions were prepared in 1/100, 1/1000th and 1:10,000, with solvents hexane, ethanolic (70%) and lyophilized aqueous extracts of Hippobroma longiflora flower. With these dilutions was assessed antibacterial and antifungal by Kirby Bauer method modified against Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923), Klebsiella pneumoniae (ATCC 13883), Pseudomonas aeruginosa (ATCC 27853) and Candida albicans (ATCC 26790). This method is based on using a filter paper disc impregnated with the test substance in the dilutions of the extracts, and then be placed in boxes Muller Hinton agar inoculated with the microorganism above reference, is carried incubation and after 24 hours reads the results evaluating the diameter of the inhibition zones. According to the methodology used, the dilutions of the plant Hippobroma longiflora part of the Flores study exhibit antibacterial and antifungal, the same results were announced in the first instance to the students and faculty of the School of Clinical Laboratory. Keywords: Hippobroma longiflora, antimicrobial, antifungal and agar diffusion.